2023
DOI: 10.3390/pharmaceutics15010220
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Study of Exosomes as Drug Delivery Systems for Bone-Related Diseases

Abstract: Bone-related diseases are major problems and heavy burdens faced by modern society. Current clinical approaches for the treatment of these pathological conditions often lead to complications and have limited therapeutic efficacy. In this context, the development of nanotherapeutic platforms, such as extracellular vesicles, can improve the relevant therapeutic effects. In particular, exosomes are nano-sized, lipid bilayer extracellular vesicles secreted by many cells in mammals. Due to their innate capacity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 141 publications
0
6
0
Order By: Relevance
“…Exosomes are one of the most popular gene delivery vehicles, especially for cartilage regeneration and repair [ 203 ]. Mao and collaborators have suggested that exosomal microRNA-92a-3p (miR-92a-3p) can regulate cartilage development and homeostasis by directly targeting WNT5A [ 204 ].…”
Section: Gene Therapy For Tissue Regenerationmentioning
confidence: 99%
“…Exosomes are one of the most popular gene delivery vehicles, especially for cartilage regeneration and repair [ 203 ]. Mao and collaborators have suggested that exosomal microRNA-92a-3p (miR-92a-3p) can regulate cartilage development and homeostasis by directly targeting WNT5A [ 204 ].…”
Section: Gene Therapy For Tissue Regenerationmentioning
confidence: 99%
“…Various techniques, such as electroporation, sonication, freeze−thaw cycling, coextrusion, and the use of surfactants, like saponin or Triton, have been employed to disrupt exosome membranes and enhance the loading efficiency of substances into EVs. 35,36 These techniques involve dissolution of membrane components and making of nanopores through interactions with the cholesterol, thereby facilitating the loading of cargo into exosomes. 37 Saponins can encapsulate hydrophobic drugs within their hydrophobic core, thereby showing a solubilizing effect.…”
Section: Approaches For Loading Cargos Into Exosomesmentioning
confidence: 99%
“…Some studies have shown that extracellular vesicles exerted a better therapeutic efficacy than the cells releasing the EVs [ 6 ]. At present, abundant sources of membrane vesicles have been developed, including various biological fluids (e.g., blood, milk [ 7 , 8 ], orange juice [ 9 ]), animal cells (e.g., mesenchymal stem/stromal cells (MSCs) [ 7 , 10 , 11 ], dendritic cells [ 12 ], macrophages [ 13 ], tumor cells [ 14 ], red blood cells [ 15 ], different animal cell lines [ 16 ], and others), plant cells (e.g., grapes, conifers, ginger, garlic, tea, etc.) [ 17 ], bacteria (e.g., intestinal flora and probiotics) [ 18 , 19 , 20 ], and others [ 21 , 22 ].…”
Section: Sources Of Membrane Vesicles For Ddssmentioning
confidence: 99%
“…As a promising tool for drug delivery, membrane vesicles have been recruited to load different types of drugs. In this Special Issue, curcumin was loaded in extracellular vesicles for neuroinflammation [ 13 ]; peroxidase and dopamine for Parkinson’s disease [ 26 ]; lncRNA H19 for osteoporosis [ 14 ]; miRNA-210 and miRNA-132 for cardiac repair [ 10 ]; paclitaxel for head and neck squamous cell carcinoma [ 23 ]; and even CRISPR/Cas9 for gene editing [ 27 ]. Similarly, different drugs were loaded by bacterial membrane vesicles as DDSs for disease treatment.…”
Section: Drug Loading Of Membrane Vesicles As Ddssmentioning
confidence: 99%
See 1 more Smart Citation